Prospective cohort study of cannabis use, predisposition for psychosis, and psychotic symptoms in young people. Issue 7481 (1st December 2004) - Henquet, Cécile; Krabbendam, Lydia; Spauwen, Janneke; Kaplan, Charles; Lieb, Roselind; Wittchen, Hans-Ulrich; van Os, Jim
Abstract: Objective To investigate the relation between cannabis use and psychotic symptoms in individuals with above average predisposition for psychosis who first used cannabis during adolescence. Design Analysis of prospective data from a population based sample. Assessment of substance use, predisposition for psychosis, and psychotic symptoms was based on standardised personal interviews at baseline and at follow up four years later. Participants 2437 young people (aged 14 to 24 years) with and without predisposition for psychosis. Main outcome measure Psychotic symptoms at follow up as a function of cannabis use and predisposition for psychosis at baseline. Results After adjustment for age, sex, socioeconomic status, urbanicity, childhood trauma, predisposition for psychosis at baseline, and use of other drugs, tobacco, and alcohol, cannabis use at baseline increased the cumulative incidence of psychotic symptoms at follow up four years later (adjusted odds ratio 1.67, 95% confidence interval 1.13 to 2.46). The effect of cannabis use was much stronger in those with any predisposition for psychosis at baseline (23.8% adjusted difference in risk, 95% confidence interval 7.9 to 39.7, P = 0.003) than in those without (5.6%, 0.4 to 10.8, P = 0.033). The risk difference in the "predisposition" group was significantly greater than the risk difference in the "no predisposition" group (test for interaction 18.2%, 1.6 to 34.8, P = 0.032). There was a dose-response relation with increasing frequency of cannabis use. Predisposition for psychosis at baseline did not significantly predict cannabis use four years later (adjusted odds ratio 1.42, 95% confidence interval 0.88 to 2.31). Conclusion Cannabis use moderately increases the risk of psychotic symptoms in young people but has a much stronger effect in those with evidence of predisposition for psychosis.